Prevalence of diarrheagenic Escherichia coli and Salmonella among poultry in Madhya Pradesh - Savita, Savita; Kusumakar, A L; Malik, Y.P.S (The Indian Journal of Animal Sciences, 2007)
A survey was conducted to know the association of various serotypes of Escherichia coli and Salmonella with diarrhoea and its source of spread among poultry in central India. Prevalence of E. coli in diarrheic fecal and environmental samples was 65.22 and 19.35%,respectively. The E. coli isolates obtained in this study belonged to 29 different serotypes with maximum frequency of serotype O25 (11.11%) belonging to enterotoxigenic group, while others were in the enteropathogenic, enterohemorrhagic, enteroaggregative and verotoxic E. coli groups. Many serotypes of E. coli obtained in this study (O4, O6, O15, O26, O44, O86, 0111 and O157) are also associated with human infections. Occurrence of salmonella in diarrheic chickens was comparatively low as only 4 Salmonella strains were obtained from diarrheic chickens and 1 from the litter sample with a prevalence of 8.69% and 3.22% respectively. Prevalence of Salmonella infection was seen up to 8 weeks of age, while E. coli infection was more up to 12 weeks of age.